Impact on Medical Students Participating in Forensic Examinations of Asylum Seekers: A Pilot Study - Katherine Blanton; Hannah Smati; Sepideh Ashrafzadeh; Dominic Schnabel; Sandy Samuel; Sana Batool; Alison Mosier-Mills; Emily Witt; Caroline Lee; J. Wesley Boyd; Katherine Peeler (Journal of Student-Run Clinics, 2023)
Background: Student-run asylum clinics handle an increasing proportion of forensic medical evaluation requests for asylum cases across the country, but the impact on medical students participating in these evaluations remains poorly understood. This study investigates the self-reported backgrounds, roles, and experiences of medical students who directly participated in forensic evaluations of asylum-seekers at a student-run forensic asylum clinic between 2017 and 2021.Methods: Electronic surveys were sent to 40 medical students who had completed at least one asylum evaluation through the student clinic. Survey questions asked about student background, motivations, volunteer roles, and learning experiences during the evaluation process. Frequencies were calculated for multiple choice and 10-point Likert scale responses. Reviewers independently identified themes in free-response answers. Responses were subsequently coded using a consensus theme bank.Results: Eighteen of 40 (45%) students emailed completed the survey. Seventy-eight percent of respondents reported a personal or familial history of immigration. Almost all wrote the first draft of the medical affidavit. All respondents to the question reported improvement in their confidence working with patients who had experienced physical or psychological trauma as a result of persecution or feared persecution, because of their participation in an asylum evaluation. Conclusions: Students frequently were motivated to participate in forensic examinations of asylum-seekers for personal reasons related to their immigrant backgrounds. Our findings suggest that asylum evaluations promote professional development and skills working with survivors of trauma, though there remain technical and emotional challenges that mandate adequate training and support for student volunteers.